In Rural Eastern Ethiopia Hearing Loss Is the Most Frequent Disability during Childhood: A Community Based Survey. - Biftu Geda; Yemane Berhane; Nega Assefa; Alemayehu Worku (PLoS ONE, 2016)
BACKGROUND:The type and extent of childhood disability in Ethiopia is unknown due to lack of accurate and reliable data. This study tried to assess the magnitude and types of disabilities among children 0-14 years of age in eastern Ethiopia. METHODS:We conducted a cross-sectional community-based study among households that are under demographic and health surveillance in eastern Ethiopia. The study population consisted of all children aged 0-14 year. A structured questionnaire was used to assess the type and severity of the disability. RESULTS:A total of 21,572 children in the age group 0-14 were screened for disability. Of which 586 (2.7%; 95% CI = 2.5%, 2.9%) had at least one kind of disability at the time of the survey. The proportion of disability increased as children were older; measured by the extended Mantel-Haenszel (M-H) chi square for linear trend (M-H = 48.74; P<0.001). Hearing impairment was the most common reported disability; 417 (71.2%; 95% CI = 67.5%, 74.9%). Among children with a disability, 179 (31.0%; 95% CI = 27.3%, 34.7%) had a combination of multiple disabilities and about a third, 200 (34.1%; 95% CI = 30.3%, 37.9%) had developed the disability during infancy. Magnitude of disability was higher among boys 335 (2.98%; 95% CIs = 2.66%, 3.30%) compared to girls 251 (2.44%; 95% CIs = 2.14%, 2.74%). CONCLUSION:Childhood disability is a health challenge in the study area and is already common at an early age. Permanent disability among children may be prevented by an early screening program in the routine child health services and adequate care, especially for hearing impairment.